Pemanfaatan Media Pembelajaran Berbasis Laboratorium Virtual PhET pada Konsep Fisika Selama Pandemi Covid-19 - Florentina Maria Panda; Albert Lumbu; Kristin O. T. Wayoi (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
The purpose of this service activity is to provide assistance to students in using Learning Media and improve students' mastery of concepts in using PhET Virtual Laboratory-Based Learning Media which is carried out in the teaching and learning process. The service method used is a descriptive method that serves to give an overview or describe the object under study through sample or population data as it is, without conducting analysis and making general conclusions. Achievements in community service activities found that assistance to students in using PhET Virtual Laboratory-Based Learning Media was proven by the enthusiasm of students in filling out Student Activity Sheets on the material Forms and Changes in Energy with an average score of 86, and increasing students' mastery of concepts in the use of PhET Virtual Laboratory-Based Learning Media carried out in the teaching and learning process is classified as very good category.